Analisis Kualitas Air Hasil Filtrasi Pengolahan Air Sekal Rumahan Berdasarkan Variasi Jumlah Arang Aktif Tempurung Kelapa (Cocos nucifera) - Baiq As'urin; Amrullah, Shafwan (Faculty of Agriculture Science & Technology, 2023)
Water is a material that is very necessary for living creatures, including humans, for daily survival. Water quality has several parameters to meet the requirements in accordance with the Republic of Indonesia Minister of Health Regulation NO 32 of 2017 so that the water is suitable and safe to use. Therefore, this research aims to characterize water from filtration results from home-scale water treatment plants using a variety of activated charcoal. The method used was a completely randomized design (CRD) with 4 treatments and 3 replications for each treatment. Based on the results of this research, variations in coconut shell activated charcoal have significantly different effects on water pH values, TDS, temperature, color and taste. Meanwhile, variations of activated charcoal did not differ significantly in the smell of water. The more variations of activated charcoal used and the longer the contact time, the better the quality of the water produced. The 700 gr activated charcoal variation is the best treatment by producing good water quality, safe and suitable for daily use.